2007
DOI: 10.2353/jmoldx.2007.060135
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mutant BRAF Alleles in the Plasma of Patients with Metastatic Melanoma

Abstract: Mutations in the BRAF oncogene at amino acid 600 have been reported in 40 to 70% of human metastatic melanoma tissues, and the critical role of BRAF in the biology of melanoma has been established. Sampling the blood compartment to detect the mutational status of a solid tumor represents a highly innovative advance in cancer medicine, and such an approach could have advantages over tissue-based techniques. We report the development of a fluorescence-based polymerase chain reaction (PCR) assay to detect mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 30 publications
1
40
1
Order By: Relevance
“…The concordance rate of cfDNA BRAF mutations with tumour BRAF mutations was 56%, which is consistent with that of other reports (Daniotti et al, 2007;Yancovitz et al, 2007). Although other groups have demonstrated the feasibility of detecting BRAF mutations in serum and plasma of patients with melanoma (Daniotti et al, 2007;Shinozaki et al, 2007;Yancovitz et al, 2007), this is the first study that compares tumour and cfDNA results from a large cohort of patients and demonstrates the potential clinical application of cfDNA mutation detection for patient selection within clinical trials.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The concordance rate of cfDNA BRAF mutations with tumour BRAF mutations was 56%, which is consistent with that of other reports (Daniotti et al, 2007;Yancovitz et al, 2007). Although other groups have demonstrated the feasibility of detecting BRAF mutations in serum and plasma of patients with melanoma (Daniotti et al, 2007;Shinozaki et al, 2007;Yancovitz et al, 2007), this is the first study that compares tumour and cfDNA results from a large cohort of patients and demonstrates the potential clinical application of cfDNA mutation detection for patient selection within clinical trials.…”
Section: Discussionsupporting
confidence: 79%
“…Yancovitz et al demonstrated BRAF mutations in cfDNA extracted from plasma of 14 of 26 (54%) stage IV melanoma patients (Yancovitz et al, 2007). Of 17 available tissue samples, the concordance of results was 10 of 17 (59%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the genetic and epigenetic changes present in the tumor tissue are represented and can be detected in the blood-borne DNA. For example, BRAF mutations can be detected in the peripheral blood of melanoma patients [7,8]. The frequent (but not invariable) association of CGI methylation with cancer, together with the relative stability of methylated genomic DNA in peripheral blood, makes it an attractive potential source of biomarkers and detection in the serum of methylated DNA from several genes has been reported.…”
Section: Epigenetics As a Source Of Biomarkersmentioning
confidence: 99%